1970
DOI: 10.1136/jech.24.1.61-d
|View full text |Cite
|
Sign up to set email alerts
|

Absence from work in relation to the length and distribution of shift hours.

Abstract: Walker, J., and de la Mare, Gwynneth (1971). Brit. J. industr. Med., 28, 36-44. Absence from work in relation to length and distribution of shift hours. A long period on night shift or even permanent night work has sometimes been suggested for those on continuous shift work to allow circadian rhythms to adapt. As the weekly hours of work have been reduced there is some evidence that a permanent night shift is practical, and about 12% of all shift workers are on this type of work. However, the case for permane… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
5
0

Year Published

1972
1972
1983
1983

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…C O N C L U S I O N S In this particular study, about 17 per cent of the total variation in absenteeism rates was accounted for by shift and the three temporal factors. However, the overall contribution of shift was not significant, which is similar to the findings of Fitzgibbons & Moch (1980) andWalker & de la Mare's (1971) comparative analysis of permanent night shift workers.…”
supporting
confidence: 89%
See 1 more Smart Citation
“…C O N C L U S I O N S In this particular study, about 17 per cent of the total variation in absenteeism rates was accounted for by shift and the three temporal factors. However, the overall contribution of shift was not significant, which is similar to the findings of Fitzgibbons & Moch (1980) andWalker & de la Mare's (1971) comparative analysis of permanent night shift workers.…”
supporting
confidence: 89%
“…h) found that shift workers had 1e.u overall absenteeism than matched day workers. In comparing permanent day workers with permanent night workers, Walker & de la Mare (1971) found no consistent differences in absence rates.…”
mentioning
confidence: 90%
“…Though having a second job was not associated strongly with repeating, again as noted by Taylor some symptomatic repeaters were stable double jobbers, while some who were rarely absent approached the irresponsible selfseeker of Hinkle et al (1961). Working overtime tended to be linked negatively with repeating, as noted by Walker and de la Mare (1971). Repeaters were a mixed bag and not homogeneous.…”
Section: Discussionmentioning
confidence: 91%
“…Those who work on rotating three-shift systems in continuous process industry, for example, have been shown to have less sickness and other absence than day workers in the same firms (Thiis-Evensen, 1958;Aanonsen, 1964;Taylor, 1967a), but a study in three factories in Germany found such shift workers' rates to be higher (Brandt, 1969). A recent comparison between day and night workers by Walker and de la Mare (1971) showed higher sickness absence rates among night workers in two out of the three firms studied.…”
mentioning
confidence: 87%